Canagliflozin in Asian patients with type 2 diabetes on metformin alone or metformin in combination with sulphonylurea. Issue 1 (14th October 2014) - Ji, L.; Han, P.; Liu, Y.; Yang, G.; Dieu Van, N. K.; Vijapurkar, U.; Qiu, R.; Meininger, G.
<x xml:space="preserve">Abstract</x> Aims To evaluate the efficacy and safety of canagliflozin, a sodium glucose co‐transporter 2 inhibitor, in Asian patients with type 2 diabetes mellitus (T2DM) inadequately controlled by metformin or metformin in combination with sulphonylurea. Methods In this 18‐week, randomized, double‐blind, placebo‐controlled phase III study, patients (N = 676) received canagliflozin 100 or 300 mg or placebo once daily. The primary efficacy endpoint was change in glycated haemoglobin (HbA1c) level from baseline at week 18. Additional endpoints included change in fasting plasma glucose (FPG) and percent change in body weight. Adverse events (AEs) were recorded throughout the study. Efficacy and safety were assessed in the overall population and in two strata based on background therapy. Results At week 18, canagliflozin 100 and 300 mg provided significant reductions from baseline in HbA1c compared with placebo (−0.97, −1.06 and −0.47%, respectively; p < 0.001). Relative to placebo, canagliflozin 100 and 300 mg also significantly reduced FPG (−1.0 and −1.4 mmol/l) and body weight [−2.2% (−1.5 kg) and −2.3% (−1.6 kg)]. Both canagliflozin doses lowered systolic blood pressure (BP) compared with placebo. The overall incidence of AEs was 38.6, 43.2 and 42.0% with canagliflozin 100 and 300 mg and placebo, respectively. The incidence of genital mycotic infections and urinary tract infections was low and similar across groups. Efficacy and safety findings in the two strata were generally consistent with the overall population. Conclusions Canagliflozin provided glycaemic improvements and reductions in body weight and systolic BP, and was generally well tolerated in Asian patients with T2DM on metformin or metformin in combination with sulphonylurea.